PENGARUH STRES KERJA, PROGRAM INSENTIF DAN MOTIVASI TERHADAP KINERJA DRIVER OJEK ONLINE - Ariq Akbar Rabbani; Wasi Bagasworo (Journal of Accounting, Management and Islamic Economics, 2024)
This study aims to examine the effect of work stress, incentive programs and work motivation of online motorcycle taxi drivers for study on Shopee Food drivers who are domiciled in DKI Jakarta. The independent variables in this study are work stress, incentive programs and work motivation. The dependent variable in this study is the performance of Shopee Food drivers. This study uses the PLS or Partial Least Square method with SmartPLS 4.0 software. The data collection technique uses the Googleform application questionnaire to collect respondent information. The sample in this study are all members of the Shopee Food driver population who live in DKI Jakarta with a total sample of 102 respondents. The results of the analysis show that work stress has no negative effect on the performance of Shopee Food drivers. The Incentive Program has a positive and significant effect on the performance of Shopee Food drivers. Work motivation has a positive and significant effect on the performance of Shopee Food drivers.